Terapi Bermain Stimulasi Motorik Anak di Panti Sosial Tuna Grahita Tomohon - Vina P.Patandung; Kansia A. Terok; Eireine M.Pandoh; Melany Kumajas; Gledys T. Lengkong (STIKES Columbia Asia Medan, 2024)
This Community Service Activity (PKM) seeks to solve complex problems faced by society or certain communities within the scope of society. Motor development is the development of elements of development and control of body movements. Motor development develops with the maturity of nerves and muscles. Motor development is also a movement that uses fine muscles that coordinate with the brain in doing something through activities such as in children playing. The influence of playing on children's development, one of which is playing which can affect the improvement of reasoning and playing their existence in the peer environment and forming reasoning and playing their existence in the peer environment and forming the imagination of children's physical development, playing can be used as therapy. One form of therapy through play is by providing stimulation or stimulation to children so that children can grow and develop optimally. Children in orphanages for the mentally disabled are children who need special attention from other people or the community, so that their growth period can run like other children in their time. In this PKM activity, the PKM team provides education in the form of direct demonstrations and interacts directly with children at the Tomohon Mentally Disabled Orphanage, to stimulate children's motoric stimuli. This PKM activity has outputs in the form of reports and article publications so that they can be accessed by everyone who needs literature in the form of related articles.